Time, talent, energy - Mankins, Michael C. (Harvard Business Review Press, 2017)
Business leaders know that the key to competitive success is smart management of scarce resources. That's why companies allocate their financial capital so carefully. But capital today is cheap and abundant, no longer a source of advantage. The truly scarce resources now are the time, the talent, and the energy of the people in your organization--resources that are too often squandered. There's plenty of advice about how to manage them, but most of it focuses on individual actions. What's really needed are organizational solutions that can unleash a company's full productive power and enable it to outpace competitors